Effective teaching strategies for dyscalculia and learning difficulties in mathematics perspectives from cognitive neuroscience - Noel, Marie-Pascale; Karagiannakis, Giannis (Routledge, Taylor & Francis Group, 2022)
"Effective Teaching Strategies for Dyscalculia and Learning Difficulties in Mathematics provides an essential bridge between scientific research and practical interventions with children. It unpacks what we know about possible cognitive causation of mathematical difficulties in order to improve teaching and therefore learning. Each chapter considers a specific domain of children's numerical development: counting and the understanding of numbers; the understanding of the base-10 system; arithmetic; word-problem solving; and understanding rational numbers. The accessible guidance includes a literature review on each topic, surveying how each process develops in children, the difficulties encountered at that level by some pupils, and the intervention studies that have been published. It guides the reader step-by-step through practical guidelines of how to assess these processes and how to build an intervention to help children master them. Illustrated throughout with examples of materials used in the effective interventions described, this essential guide offers deep understanding and effective strategies for developmental and educational psychologists, special educational needs and/or disabilities coordinators and teachers working with children experiencing mathematical difficulties"